The Effects of Types of Manure and Mycorrhizal Applications on Sandy Soils on the Growth and Yield of Curly Red Chili (Capsicum annum L.) - Putra, Sukmana Siswandana; Putra, Eka Tarwaca Susila; Widada, Jaka (Universitas Sebelas Maret, 2020)
Market demand for chilies continues to increase, so efforts are needed to increase the productivity of the chili plants. One of the efforts is by intensifying production factors such as applying fertilizers on beach sand which contain low nutrients and organic matter so that manure input is needed and also utilizes soil microbial technology in the form of arbuscular mycorrhizal fungi which are relatively cheap economically and environmentally friendly. The purpose of this research was to study the effect of types of manure and mycorrhizal applications on the growth and yield of curly red chili. The research was arranged in a strip-plot Randomized Completely Block Design (RCBD) consisting of two factors with three replications. The first factor is the type of fertilizer (cow manure, chicken manure, guano fertilizer, quail manure and urea fertilizer) and the second factor is the application of mycorrhizae (with and without). This study concludes that quail manure increases plant height. The addition of chicken manure, guano fertilizer and quail manure multiplies the total fruit production. The application of mycorrhizae gives the same results on the growth and yield of chili.